Unveiling the potential of Butylphthalide: inhibiting osteoclastogenesis and preventing bone loss - Feng Yanbin; Feng Yanbin; Teng Yilin; Mo Yaomin; Xi Deshuang; Zhou Junhong; Zeng Gaofeng; Zong Shaohui; Zong Shaohui (Frontiers Media S.A., 2024)
Osteoporosis, resulting from overactive osteoclasts and leading to elevated fracture risk, has emerged as a global public health concern due to the aging population. Therefore, inhibiting osteoclastogenesis and bone resorption function represents a crucial approach for preventing and treating osteoporosis. The purpose of this study was to examine the effects and molecular mechanisms of Butylphthalide (NBP) on the differentiation and function of osteoclasts induced by RANKL. Osteoclastogenesis was assessed through TRAP staining and bone slice assay. An animal model that underwent ovariectomy, simulating postmenopausal women's physiological characteristics, was established to investigate the impact of Butylphthalide on ovariectomy-induced bone loss. To delve deeper into the specific mechanisms, we employed Western blot, PCR, immunofluorescence, and immunohistochemical staining to detect the expression of proteins that are associated with the osteoclast signaling pathway. In this study, we found that Butylphthalide not only suppressed osteoclastogenesis and bone resorption in vitro but also significantly decreased TRAcP-positive osteoclasts and prevented bone loss in vivo. Further mechanistic experiments revealed that Butylphthalide reduces intracellular ROS in osteoclasts, inhibits the MAPK and NFATc1 signaling pathways, and downregulates the key genes and proteins of osteoclasts. This inhibits osteoclast formation and function. The reduction in ROS in osteoclasts is intricately linked to the activity of Butylphthalide-modulated antioxidant enzymes. Overall, NBP may offer a alternative treatment option with fewer side effects for skeletal diseases such as osteoporosis.